The procalcitonin/albumin ratio as an early diagnostic predictor in discriminating urosepsis from patients with febrile urinary tract infection. Issue 28 (July 2018) - Luo, Xin; Yang, Xiang; Li, Jiexian; Zou, Ge; Lin, Yufeng; Qing, Guoqiang; Yang, Ruilin; Yao, Weixiang; Ye, Xuying
Abstract : Abstract: Discrimination between urosepsis and febrile urinary tract infections is important in therapeutic decision-making to indicate suitable treatments to avoid sepsis-related organ failure. Accurate diagnosis is time-consuming and susceptible to false-positive results. Moreover, patient responses to urosepsis are complex and varied. Therefore, this study aimed to develop a new, early diagnostic predictor that could discriminate between patients with urosepsis and those with febrile urinary tract infections using a combination of initial procalcitonin and albumin levels. We conducted a retrospective study involving 140 patients with febrile urinary tract infections from January 2013 to December 2017. Univariate and multivariate logistic analyses were performed to identify the independent risk factors for differentiating urosepsis from febrile urinary tract infection. A receiver operating characteristic (ROC) curve analysis was conducted to compare the predictive accuracy of the procalcitonin/albumin ratio. Patients in the urosepsis group had higher procalcitonin/albumin ratios compared to those in the febrile urinary tract infection group [2.254 (0.978, 6.299) vs 0.021 (0.004, 0.095); P < .001]. Based on multivariate logistic analysis, the procalcitonin/albumin ratio [adjusted odds ratio (OR) 1.029, 95% confidence interval (CI) 1.013–1.045, P < .001] was an independent predictor of urosepsis, which allowed for differentiation from patients with febrile urinary tract infections. The area under the ROC curve (AUC) for the procalcitonin/albumin ratio was 0.937 (95% CI, 0.894–0.980); P < .001. The sensitivity and specificity of the procalcitonin/albumin ratio cut-off values (>0.44) were 84.62% and 96.00%, respectively. Moreover, in the subset of 65 patients with urosepsis, the procalcitonin/albumin ratio in the uroseptic shock group was higher than in the group of patients without uroseptic shock [5.46 (1.43, 6.58) vs 1.24 (0.63, 4.38); P = .009]. Our study demonstrates that the procalcitonin/albumin ratio is an early diagnostic predictor that can discriminate between urosepsis and febrile urinary tract infection. Additionally, in patients with urosepsis, those with higher procalcitonin/albumin ratios were more prone to uroseptic shock. Our findings suggest that the procalcitonin/albumin ratio is a rapid and relatively low-cost biomarker that can be used in clinical practice.